Searching for an Effective Way to Farm Accounting for Career Development: A Case Study of Khlong Tanod Community, Min Buri District, Bangkok - Saithong-in, Supapan; Jaimuk, Phimpaka; Benjasewee, Punnapa (Rajapark Journal, 2024)
The purposes of this research were to study basic accounting knowledge and farm accounting and find an appropriate way of recording, analyzing, reporting, and utilizing farm accounting information for decision-making to create a farm accounting model suitable for the context of the Khlong Tanod community. This participatory action study uses surveys, interviews, discussions, group discussions, and knowledge-formulation activities. The study revealed that the community has a basic understanding of accounting, recognizing it as the process of recording daily financial activities and tracking monthly balances. However, they do not record their income and expenses. This lack of record-keeping stems from a general lack of concern and knowledge about accounting, as they believe that their income and expenditures are not significant enough to warrant documentation. During the production of mushroom chili paste, the process becomes a community-based business. As a result, the community recognizes the importance of accounting and has started efforts to improve their accounting knowledge. This initiative includes learning about accounting for both daily life and community business activities. The community jointly designed accounting records to serve community businesses, resulting in seven essential accounting books. These include a cash book, a product sales book, a raw material purchase book, a product cost calculation book, an inventory control book, an expense book, and a performance report book. Additionally, there is a manual on farm accounting for community groups.